Fifty Years of Research and Development Coming to Fruition; Unraveling the Complex Interactions during Processing of Transparent Magnesium Aluminate (MgAl2O4) Spinel. Issue 11 (November 2013) - Rubat du Merac, Marc; Kleebe, Hans‐Joachim; Müller, Mathis M.; Reimanis, Ivar E.
Abstract : The need for materials for demanding optical applications has engendered a resurgent interest in transparent ceramics. Transparent polycrystalline magnesium aluminate spinel is one especially promising and rapidly maturing technology that can fill this niche. Although it has been studied for over 50 yr, it is only recently that highly transparent components with acceptable mechanical properties have been reliably fabricated at reasonable cost. Development has been hindered by the inherent difficulty in sintering spinel to the near‐theoretical density required for transparency, a high sensitivity to powder and processing parameters, variable stoichiometry, and a lack of understanding of the synthesis–processing–property relationships. The driver of recent success is an emerging understanding of complex, multiscale, multivariable interactions that occur during green‐body formation and sintering. In particular, certain key variables play a decisive role in determining compact properties and their evolution must be controlled from synthesis to the finished product. This article features the interactions between these key variables during processing and gives an exposé of the state of the art in transparent polycrystalline spinel fabrication.